Penerapan Strategi Hybrid On-Chain/Off-Chain dalam Penyimpanan Data Pasien Rumah Sakit pada Jaringan Blockchain - Salman El Farisi; Yaasir Aidil Fitrah; Fatiah Al Zahra; Akhmam Fahmi (Jurnal Teknologi Terpadu, 2026)
In recent years, the adoption of Electronic Medical Records (EMR) has become an important part of the digital transformation in the healthcare sector. However, centralized EMR systems still face several challenges, including the risk of single points of failure and limitations in ensuring the integrity and security of patient data. This research aims to develop a prototype of a decentralized RME data storage system utilizing Blockchain and the Inter-Planetary File System (IPFS). The system is designed to support three main scenarios, namely patient registration, patient data search, and outpatient registration. Patient medical record data is stored off-chain on IPFS in JSON format, while metadata, including the Content Identifier (CID) and Population Identification Number (NIK), is stored on-chain on the Ethereum network using Smart Contracts. System evaluation was conducted by measuring gas consumption in patient data storage and outpatient registration functions. The results show that the patient registration function consumes a significantly higher average gas (380,907 units) than the outpatient registration function (51,540 units), indicating greater computational complexity. These findings also suggest that integrating blockchain technology with IPFS is a viable approach to building a secure, decentralized electronic medical record (EMR) storage system.